An Investigation into the Use of Repetition (Rhetorical Figure) in Vietnamese TV Commercials = Điều tra việc sử dụng phép lặp (biện pháp tu Từ) trong quảng cáo truyền hình tiếng việt - Lê, Tuấn Anh (2021)
Repetition is one of the most popular rhetorical figures used in language of advertising in general and TV advertisement in particular. Thanks to the use of this figure, the language of commercials becomes more attractive, listenable, memorable and persuasive. However, there is a fact that not many researchers have investigated this issue, especially in Vietnam. The research focuses on the use of repetition patterns of rhetorical figure in Vietnamese TV commercials. From that point, the effectiveness of each is also drawn and elaborated, which, to a certain degree, helps advertising agencies construct more effective advertising strategies. To investigate the use of repetition just in Vietnamese commercials, 40 commercials in Vietnamese was collected randomly from major TV channels such as VTV1, VTV2, HTV7, etc. After completing the data collection, all commercials were observed carefully and transcribed on the basis of transcription conventions. After that, they were analyzed and discussed thoroughly, basing mainly on the personal observation in combination with the descriptive statistics. The research pointed out the 8 patterns of repetition of rhetoric device employed in Vietnamese TV commercials as well as the effectiveness of each reflected through findings and data analysis.